Sujuvat tieto- ja viestintätekniikan taidot edesauttavat oppimista verkko-oppimisympäristössä - Leivo-Rintakorpi, Tuija (2018)
The work is based on a questionnaire survey, focused to employees of the organization of one trained stakeholder in the Population Register Center. 118 people answered the questionnaire. Most of the respondents were over 46 years old and had worked for more than 10 years for the same employer. Based on the results of the research, more than half of the respondents did not have experience of studying in an online learning environment. Based on the results, videos as e-learning material supports learning best, and pedagogical guidance skill are expected from the online teachers. Network interaction was considered important. Based on the survey, H5P tools in Moodle can be used to build interactive digital learning materials.